Designing a Microstrip Patch Antenna in Part of Ultra-Wideband Applications (Baghdad Science Journal, 2020)
In this work, a simulated study was carried out for designing a novel spiral rectangular patch of microstrip antenna that is used in ultra-wideband applications by using a high frequency structure simulator software (HFSS). A substrate with dielectric constant of 4.4 and height 2.10 mm (commercial substrate height available is about 0.8-1.575 mm) has been used for the design of the proposed antenna. The design basis for enhancing bandwidth in the frequency range 6.63 - 10.93 GHz is based on increasing the edge areas that positively affect the antenna's efficiency. This design makes the designed antenna cost less by reducing the area of the patch. It has been noticed that the bandwidth of the antenna under this study is increasing to 4.30 GHz or 61% compared with 3.6% for the standard rectangular microstrip antenna with the same dimensions of the proposed antenna. The antenna also maintains the voltage standing wave ratio of 1.09 at resonant frequency 7.07 GHz, return loss -27.07 dB, and the amount of impedance in real and imaginary parts 51.5Ω and 3.3Ω, respectively.